Pengaruh Likuiditas, Struktur Modal, Ukuran Perusahaan, Prospek Pertumbuhan, Kualitas Audit Terhadap Kualitas Laba Perusahaan Batu Bara - Chandra Ferdinand Wijaya (JEMAP, 2020)
Financial statements are a means used by company’s management to communicate financial information to its users in order to assist decision making. Company’s management has more information than shareholders. As a result, company’s management tends to make earnings management for certain purposes. Such conditions reduce the quality of earnings presented in the financial statements. Some factors are expected to influence the tendency of companies to manipulate earnings that affect earnings quality. The purpose of this research is to examine the effect of liquidity, capital structure, company size, growth prospects, and audit quality on earnings quality. This research is a causal research. The population consists of coal mining sub-sector companies listed in Indonesia Stock Exchange during 2012 - 2016. This research uses simple random sampling and analysed by multiple linear regression. The result shows that liquidity, capital structure, company size, growth prospects, and audit quality have a significant effect simultaneously on earnings quality. The partial hypothesis testing shows that liquidity has no significant effect on earnings quality, while firm size and audit quality have a significant positive effect on earnings quality. The capital structure and growth prospects have a significant negative effect on earnings quality.